Innovation and competition in Internet and mobile banking: an industrial organization perspective - Carlotta Mariotto; Marianne Verdier (Bank of Finland, 2015)
Over the recent years, the development of Internet banking and mobile banking has had a considerable impact on competition in the retail banking industry. In some countries, the regulatory framework has been adapted to allow non-banks to operate in retail payments and compete with banks for deposits. Several platforms or large retailers have started to offer innovative financial products to their customers. In this paper, we survey the issues related to innovation and competition in Internet banking and mobile banking and discuss some perspectives for future research.
URN:NBN:fi:bof-201511261452
Keywords: E42; G21; L96; 330